Implementation of the School Literacy Movement (GLS) during the Covid-19 Pandemic in Elementary Schools - Nugraha, Fivo (Journal of Language, Literature and Teaching, 2023)
The implementation of school literacy movement (GLS) activities during the pandemic encountered challenges. The activities that are usually carried out in school, now students have to learn from home. Every school is required to adapt and innovate during this pandemic, including school that hold GLS activities. The importance of GLS activities on student literacy, make school have to do maximal effort so that the activities still going on.The use of technology is one  solution to become a supporting tool for GLS activities during the pandemic. This study aims to find out the implementation of literacy activities in elementary school during the pandemic. The method used in this study is a systematic review. In implementation, school that continue to carry out GLS activities are school that innovate, school that carry out good management and use technology as a tool.